Pembentukan Pendidikan Berkarakter Pada Peserta Didik SMK Negeri 7 Denpasar - Pramandhita, I Kadek Panji; Sumeryasa, I Gede; Kusuma, Ilham Maulana; Giri, I Gede Mantre Bimantara; Khesyawa, I Komang Yuma (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Character education in vocational high schools is essential to produce graduates who are not only technically competent but also morally upright in a globalised world. At SMK Negeri 7 Denpasar, however, character programmes face obstacles such as students’ low awareness, limited parental involvement, and negative social-media influence. This study evaluates the current character-education practices and designs improvement strategies using a design-thinking approach. Data were obtained from teacher–student interviews and processed through data display, reduction, empathy mapping, and pain-gain analysis to identify root problems. Ideation yielded two priority solutions: (1) a structured outreach programme emphasising the relevance of character values for employability, and (2) regular discussion–reflection sessions using stories to internalise morals. Pilot implementation indicated higher student engagement and greater teacher ease when digital media were integrated. The findings confirm design thinking’s effectiveness for generating collaborative solutions among schools, families, and communities, while offering a replicable model for strengthening character education in other Indonesian vocational schools.